Students’ Perceptions of Using Mobile Legends: Bang Bang for English Vocabulary Learning - Suci Prihatiningtyas; Istiqomatus Sa’diyah; Septiana Putri Rahmawati; Hanifah Hanifah; Akhmad Kanzul Fikri; Yuyun Bahtiar (SCHOOLAR: Social and Literature Study in Education, 2026)
This study aims to analyze students’ perceptions of the use of the game Mobile Legends: Bang Bang in English vocabulary learning. The study employed a quantitative approach using a descriptive survey design. The participants consisted of 30 eleventh-grade students of SMK Unggulan NU Mojoagung, Jombang, selected through cluster sampling. Data were collected using a questionnaire with a five-point Likert scale and analyzed using descriptive statistics, including mean scores and percentage distribution. The results showed that the overall mean score was 3.65, categorized as high, indicating that students have positive perceptions of the use of digital games in vocabulary learning. Most responses were dominated by the Agree and Strongly Agree categories, suggesting that students perceive the game as providing contextual language exposure and supporting incidental learning. Students also demonstrated the ability to understand, remember, and apply vocabulary encountered in the game. However, not all students fully agreed that games could function as formal learning media, indicating the influence of individual factors such as learning styles, motivation, and perceptions.In conclusion, digital games have strong potential as alternative media for English vocabulary learning, but their use should be integrated with structured instructional strategies to achieve optimal learning outcomes.